2018
DOI: 10.1038/s41467-018-07584-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific biological and molecular profiling distinguishes paediatric from adult acute myeloid leukaemias

Abstract: Acute myeloid leukaemia (AML) affects children and adults of all ages. AML remains one of the major causes of death in children with cancer and for children with AML relapse is the most common cause of death. Here, by modelling AML in vivo we demonstrate that AML is discriminated by the age of the cell of origin. Young cells give rise to myeloid, lymphoid or mixed phenotype acute leukaemia, whereas adult cells give rise exclusively to AML, with a shorter latency. Unlike adult, young AML cells do not remodel th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 54 publications
(54 reference statements)
2
42
0
1
Order By: Relevance
“…Experiments based on transplantation of fetal liver- or BM-derived cells retrovirally expressing the NUP98–HOXA9 fusion into adult recipients revealed that the age of the cell of origin determines not only the latency period for disease development but also the lineage phenotype and changes of the BM niche (89). In the attempt to model Trisomy 21-associated AMKL, retroviral expression of ERG in murine adult BM leads to 100% of T-cell leukemia, while expression in E12.5 fetal liver cells generated erythro-megakaryocytic leukemia in 40–60% of recipient mice (90).…”
Section: Modeling Genetic Lesions In Pediatric Amlmentioning
confidence: 99%
“…Experiments based on transplantation of fetal liver- or BM-derived cells retrovirally expressing the NUP98–HOXA9 fusion into adult recipients revealed that the age of the cell of origin determines not only the latency period for disease development but also the lineage phenotype and changes of the BM niche (89). In the attempt to model Trisomy 21-associated AMKL, retroviral expression of ERG in murine adult BM leads to 100% of T-cell leukemia, while expression in E12.5 fetal liver cells generated erythro-megakaryocytic leukemia in 40–60% of recipient mice (90).…”
Section: Modeling Genetic Lesions In Pediatric Amlmentioning
confidence: 99%
“…These mutations are common in adult AML but rare in paediatric patients, highlighting differences in leukaemogenesis between these patient populations. In line with this, differences in leukaemic phenotype and latency were shown to be highly dependent on cellular age in a murine model (Chaudhury et al , ).…”
Section: Epigenetic Regulation In Normal Haematopoiesismentioning
confidence: 73%
“…Other remarkable differences between pediatric and adult AMLs are represented by: (a) in children, the large majority of patients present with de novo AMLs, while in adults, a significant proportion of AMLs arises from an underlying MDS or myeloproliferative neoplasm; (b) in pediatric AML, only 20% of cases have a normal karyotype and the number of somatic mutations is lower than in adult [41,42]. Studies in animal models clearly showed that pediatric AML is biologically different to adult AML, and that the age of the cell of origin clearly influences leukemia latency, lineage, molecular profile, and the leukemic microenvironmental niche [43].…”
Section: Acute Myeloid Leukemia (Aml)mentioning
confidence: 99%